2002
DOI: 10.1021/jp0132782
|View full text |Cite
|
Sign up to set email alerts
|

FTIR Study of CO Adsorption on Ni−ZSM-5

Abstract: Adsorption of CO on Ni-ZSM-5 reveals the existence of two kinds of Ni 2+ ions, with the respective stretching frequencies being at 2220 and 2212 cm -1 . The carbonyl complexes are resistant to evacuation at room temperature, which is explained by the high electrophilicity of cations in a ZSM matrix. At 85 K and in the presence of CO, part of the Ni 2+ -CO species are converted into Ni 2+ (CO) 2 dicarbonyls (2204 cm -1 ) which are characterized by a very low stability and easily lose one of their CO ligands. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
174
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(203 citation statements)
references
References 41 publications
29
174
0
Order By: Relevance
“…These analyses revealed that there are two types of interactions for CO adsorption at Co oct and O 2f sites, namely s-donation and p*-back-donation, and the latter is responsible for the observed red-shift. The CO red-shift and the same bonding mechanism have been reported in a number of theoretical (CO/CuCr 2 O 4 (100), [42] CO/Cu 2 O(111), [43,44] CO/Al 2 O 3 [45] ) and experimental (CO/Co 3 O 4, [39] CO/Ni-ZSM-5 [46,47] ) studies. On the Co 3 O 4 (110)-B defect surface with an O 2f vacancy, CO adsorbs at the O 2f -vac site through carbon.…”
Section: Vacancy Formation Energy Of Co 3 O 4 (110)-b Surfacesupporting
confidence: 75%
“…These analyses revealed that there are two types of interactions for CO adsorption at Co oct and O 2f sites, namely s-donation and p*-back-donation, and the latter is responsible for the observed red-shift. The CO red-shift and the same bonding mechanism have been reported in a number of theoretical (CO/CuCr 2 O 4 (100), [42] CO/Cu 2 O(111), [43,44] CO/Al 2 O 3 [45] ) and experimental (CO/Co 3 O 4, [39] CO/Ni-ZSM-5 [46,47] ) studies. On the Co 3 O 4 (110)-B defect surface with an O 2f vacancy, CO adsorbs at the O 2f -vac site through carbon.…”
Section: Vacancy Formation Energy Of Co 3 O 4 (110)-b Surfacesupporting
confidence: 75%
“…This led to the presence of cationic Ni. The bands at 2210-2212 cm À1 are assigned to Ni 2 + À CO, [24][25][26][27] whereas the two bands at 2136-2137 and 2092-2094 cm À1 are ascribed to the symmetric and asymmetric CO stretching of geminal Ni + (CO) 2 dicarbonyls. [21,22,28,29] The Ni + ion is speculated to originate from the reduction of Ni 2 + in the reducing environment of CO. [30] The fact that two CO molecules are attached to one Ni + cation compared with Ni 2 + À CO can be rationalized by the higher ionic radius of Ni + .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in a precedent work Yashima et al [16] [19,20,21,22,24], reduction with H 2 [22] or CO at high temperatures (350-450ºC), [21,25,26], or even upon contact of the catalyst with ethylene [19,20]. It is pertinent to mention here that in most of the above studies the conclusion that monovalent Ni + species are the active sites relied on room temperature CO-FTIR characterization results [12,19,20,21,24].…”
Section: Nature Of Active Ni Sites In Ni-beta Catalystsmentioning
confidence: 99%